Peranan Tokoh Adat Sebagai Mediator terhadap Pernikahan Adat Lampung dalam Perspektif Hukum Keluarga Islam - Nugara Adi Saputra (Institut Agama Islam Negeri Metro, 2025)
The traditional marriage customs of the Lampung community, particularly the sebambangan tradition, constitute an essential aspect of its socio-cultural structure. This study investigates the role of traditional leaders in resolving marital disputes within Lampung’s customary framework through mediation based on Islamic family law principles. Using a qualitative method, the research draws on in-depth interviews with traditional leaders in Gunung Haji Village, namely Mr. Dendi Sepriyadi, Mr. Ahmad Nasoha, and Mr. Sidik. The findings indicate that traditional leaders occupy a pivotal role in reconciling conflicts by integrating the values of customary law with the normative framework of Islamic family law. They serve as both implementers of local traditions and mediators who ensure alignment with Islamic teachings. Additionally, their involvement contributes to cultural continuity by providing education and moral guidance to the younger generation. This study concludes that the mediatory role of traditional leaders is instrumental in achieving justice and social harmony within traditional marriage systems, offering a model of legal pluralism that bridges Islamic norms with local wisdom.